2017
DOI: 10.1002/cncr.30842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of recommendations for screening mammography using CISNET models

Abstract: CISNET models demonstrate that the greatest mortality reduction is achieved with annual screening of women starting at age 40 years. Cancer 2017;123:3673-3680. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
64
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 24 publications
0
64
0
1
Order By: Relevance
“…The ACR recommendation for annual screening starting at age 40 years and ending at age 84 years was found to have a greater benefit in breast cancer mortality reduction in both analyses compared with that of the USPSTF (biennial, ages 50‐74 years) (38/26 vs 40/23), as would be expected. Arleo et al did not provide the incremental benefit of annual screening beyond age 74 years in terms of relative or absolute risk reduction. The previous CISNET modeling of overdiagnosis in this older age group did not use annual screening and did not account for resource costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ACR recommendation for annual screening starting at age 40 years and ending at age 84 years was found to have a greater benefit in breast cancer mortality reduction in both analyses compared with that of the USPSTF (biennial, ages 50‐74 years) (38/26 vs 40/23), as would be expected. Arleo et al did not provide the incremental benefit of annual screening beyond age 74 years in terms of relative or absolute risk reduction. The previous CISNET modeling of overdiagnosis in this older age group did not use annual screening and did not account for resource costs.…”
mentioning
confidence: 99%
“…Arleo et al used Cancer Intervention and Surveillance Modeling Network (CISNET) computer modeling to compare the benefit and harms from 3 different screening recommendations from the American College of Radiology (ACR), the American Cancer Society (ACS), and the US Preventive Services Task Force (USPSTF) . Mandelblatt et al modeled multiple screening strategies ending at age 74 years and by comparing life‐years gained with mammograms performed found that both the ACR and USPSTF strategies were efficient, whereas hybrid strategies such as that of the ACS were not .…”
mentioning
confidence: 99%
“…We thank Dr. Keen for responding to our article . Much of his response is regarding cost, which is beyond the scope of our article and to our knowledge is not discussed in any of the national organization screening guidelines.…”
mentioning
confidence: 99%
“…Keen's letter is overdiagnosis. We explicitly stated in the “Methods” section why our article did not discuss overdiagnosis: “Because both CISNET [Cancer Intervention and Surveillance Modeling Network] modelers and the USPSTF [US Preventive Services Task Force] acknowledge that ‘methods for estimating overdiagnosis at a population level are not well established’ and ‘Existing science does not allow for the ability to determine precisely what proportion of cancer diagnosed by mammography today reflects overdiagnosis, and estimates vary widely depending on the data source and method of calculation used,’ the decision was made not to include overdiagnosis in this study's risk assessment.” However, because Dr. Keen raises the issue, we would like to stress that overdiagnosis is not reduced by screening less frequently or by initiating screening at a later age.…”
mentioning
confidence: 99%
See 1 more Smart Citation